Father Involvement in Early Childcare: review of the literature - Sari, Muthia (International Conference on Elementary Education, 2020)
In general, fathers are the main breadwinners in the family. Fathers busy at work has an impact on the reduced time that fathers can spend with their children. It also makes more fathers have to surrender childcare to mothers. Whereas previous studies have revealed that the involvement of fathers in early child care provides benefits for father-child relationships, and in the growth and development aspects of children. This paper will describe how the involvement of fathers in childcare. This article also aims to provide an understanding of the role of fathers in childcare, what factors influence the involvement of fathers in parenting, and the benefits that can be derived from the process of father involvement in early childcare